Pengaruh Rasio CAR, LDR, ROA, ROE, NIM, BOPO Terhadap NPL di Bank Pembangunan Daerah di Sumatera - Yasmir, Yasmir; Widyastuti, Ira; Marlina, Eva (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to evaluate the relationship between the variables of Capital Adequacy Ratio (CAR), LDR (Loan to Deposit Ratio), ROA (Return on Assets), Return on Equity (ROE), Net Interest Margin (NIM), and Operating Expenses to Operating Income (BOPO) with Non-Performing Loans (NPL), and to identify other potential factors influencing NPL. This research involves the analysis of data from 40 bank samples in Sumatra. The data analysis techniques used include significance tests, multicollinearity tests, heteroscedasticity tests, and regression analysis to understand whether the Capital Adequacy Ratio and other variables have a significant impact on Non-Performing Loans, as well as to explore the strengths and weaknesses of the regression model used. The results indicate that CAR has a significant relationship with NPL, while other variables such as LDR, ROA, ROE, NIM, and BOPO do not show a significant influence. The regression model demonstrates a strong correlation between the independent variables and NPL, with approximately 41.8% of the variation in NPL being explained by the independent variables in the model. Nonetheless, other factors need to be considered to fully understand the variation in NPL